2016
DOI: 10.1002/2015pa002903
|View full text |Cite
|
Sign up to set email alerts
|

The “warm” Marine Isotope Stage 31 in the Labrador Sea: Low surface salinities and cold subsurface waters prevented winter convection

Abstract: Surface and subsurface conditions in the Labrador Sea during Marine Isotope Stage (MIS) 31 at the Integrated Ocean Drilling Program Site U1305 off southwest Greenland are reconstructed based on dinocyst and foraminifer assemblages. Isotopic compositions of planktonic (Neogloboquadrina pachyderma, Np) and benthic (Cibicides wuellerstorfi, Cw, and Oridorsalis umbonatus, Ou) foraminifera provide further information about water properties in the mesopelagic layer as well as at the seafloor. Dinocyst proxy reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Warmer conditions, with values as high as 5 °C are depicted in the NH polar region in agreement with palaeoreconstruction (Raymo et al 1996;Lawrence et al 2009;Melles et al 2012;Aubry et al 2016). This is supported by the reduced sea-ice extension and thickness due to the influence of the precessional cycle (Fig.…”
Section: Differences Between Mis 31 and Ctr Climatessupporting
confidence: 79%
See 1 more Smart Citation
“…Warmer conditions, with values as high as 5 °C are depicted in the NH polar region in agreement with palaeoreconstruction (Raymo et al 1996;Lawrence et al 2009;Melles et al 2012;Aubry et al 2016). This is supported by the reduced sea-ice extension and thickness due to the influence of the precessional cycle (Fig.…”
Section: Differences Between Mis 31 and Ctr Climatessupporting
confidence: 79%
“…It should be noted that the Kurushio-Oyashio SST is an important source of heat contributing to the Northern Pacific climate variability and PDO magnitude (Trenberth et al 1998). A brief comparison with palaeoreconstruction shows that the seasonal temperature contrast in the NH was also reported by Aubry et al (2016). They claimed that cold subsurface and warm surface waters in the Labrador Sea associated with low salinity prevented winter oceanic convection (Fig.…”
Section: Differences Between Mis 31 and Ctr Climatesmentioning
confidence: 86%
“…It was shown that multivariate statistical analyses performed with paleo and modern cyst assemblages could be used to reconstruct these parameters in the Late Quaternary [e.g. de Vernal et al, 2001de Vernal et al, , 2005de Vernal et al, , 2013Radi and de Vernal, 2008;Pospelova et al, 2015;Aubry et al, 2016;Hardy et al, 2018]. Most of these studies were focused on the LGM and the Holocene in the North Atlantic, and published data on dinoflagellate cysts during the LIG are less common in general and are again mainly located in the North Atlantic [e.g.…”
Section: Dinoflagellate Cystsmentioning
confidence: 99%